Digest: Avian genomes are permeable to introgression for a few million years. (1st May 2020) - Ottenburghs, Jente
Abstract: How wide is the time window for introgression after divergence? Pulido‐Santacruz et al. addressed this question by studying the evolutionary history of the bird genus Dendrocincla . They found five introgression events that occurred between a few hundred thousand and around 2.5 million years after divergence. The introgressed genomic proportion declined exponentially with the age of the hybridizing taxa. Hence, this study suggests that species boundaries are permeable up to 2.5 million years after divergence.